The roles of male persistence and aggression in male-male and male-female interactions in Drosophila melanogaster - Baxter, Carling (My University, 2019)
All animals face a complex environment full of obstacles that they must overcome in order to survive and reproduce. How an individual responds to its environment is essential to overcoming such obstacles in order to maximize fitness. In my thesis, I focused on the roles of persistence and aggression in achieving fitness-relevant goals. Persistence is continuing in a course of action in spite of difficulty or resistance, and aggression is any instance where an individual uses physical, and potentially damaging, force against a conspecific. I used fruit flies (Drosophila melanogaster) as a model system to examine the ways in which males use persistence and aggression to attain fitness-relevant goals such as defending resources, gaining access to females, and mating. I first examined how a male’s age affected his persistence in courting recently mated females, who are generally unreceptive, and found that older males were more persistent than younger males (Chapter 2). Next, I showed that males of different ages differed in their courtship persistence in the presence of a competitor, and that males were able to subtly, but directly, interfere with one another’s courtship attempts (Chapter 3). I then demonstrated how males were able to use aggression in a mate guarding context to reduce the likelihood that a competitor male mated with their recent mate (Chapter 4), and as a form of resource defense to defend a desirable food patch in the presence of a potential mate (Chapter 5). Finally, I considered male persistence in the pursuit of unreceptive females as a form of male sexual aggression towards recently mated and sexually immature females (Chapters 5 and 6). Overall, my thesis work demonstrates how complex, and sometimes intertwined, the roles of persistence, aggression, and sexual coercion can be even within a ‘simple’ model organism, such as the fruit fly.
Persistence and aggression in Drosophila melanogaster
Keywords: Aggression; Persistence; Drosophila; Fruit flies; Resource defence; Forced copulation